Adjuvant agents in regional anaesthesia. Issue 12 (December 2021) - Gallagher, Mark; Grant, Calum RK
Abstract: The addition of adjuvant agents to intrathecal and epidural anaesthetic techniques is well established, in particular opioids and clonidine. These adjuvants are utilized to improve the quality of anaesthesia and analgesia. Several other adjuvants have been studied but ongoing concerns surrounding safety and efficacy may limit their use in clinical practice. Epinephrine has for many years been administered in combination with local anaesthetic although more recently a diverse range of adjuvants have been added to peripheral nerve block solutions, again with the aim of prolonging surgical anaesthesia. The evidence to support or refute the benefit of these agents is increasing, as is our understanding of which agents have demonstrable efficacy and safety at clinically appropriate doses. Clinicians must be aware that many adjuvants are not licensed for central neuraxial or perineural use and should be aware of the risks, in particular of neurotoxicity and unwanted side effects.